Hydrocarbon adsorbent, exhaust gas purification catalyst and exhaust gas purification system
By containing a porous zeolite with a specific metal outside the zeolite framework as a hydrocarbon adsorbent, the problem of existing catalysts not purifying hydrocarbons under high temperature conditions is solved, and efficient hydrocarbon removal and catalyst purification are achieved.
Patent Information
- Application Number
- CN202180059669.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-31
- Filing Date
- 2021-07-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-29
AI Technical Summary
The existing cold start catalysts cannot effectively maintain stored hydrocarbons under high temperature conditions, resulting in the hydrocarbons being discharged before purification.
Porous zeolites containing specific metals outside the zeolite framework are used as hydrocarbon adsorption materials, and hydrocarbons can be adsorbed and stored at a higher temperature and desorbed at the temperature of catalyst activation.
The hydrocarbon removal performance is improved, the catalyst purification efficiency is enhanced, and the hydrocarbon adsorbent has excellent heat resistance.
Smart Images

Figure CN116157191B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrocarbon adsorbing material capable of adsorbing and storing hydrocarbons in exhaust gas exhausted from an internal combustion engine such as an automobile, an exhaust gas purification catalyst, and an exhaust gas purification system. Background Art
[0002] The exhaust gas from internal combustion engines such as cars that use gasoline as fuel contains harmful components such as hydrocarbons (HC) from unburned fuel, carbon monoxide (CO) caused by incomplete combustion, and nitrogen oxides (NOx) caused by excessive combustion temperatures. Exhaust gas purification catalysts are used to treat such exhaust gas from internal combustion engines. Such exhaust gas purification catalysts oxidize, for example, hydrocarbons (HC) into water and carbon dioxide (CO2), oxidize, and convert CO into CO2, and reduce, and convert NOx into nitrogen gas for purification. Such exhaust gas purification catalysts use, for example, platinum group metals, among which platinum group metals such as platinum (Pt), palladium (Pd), and rhodium (Rh) are particularly used. In addition, as a constituent component of the exhaust gas purification catalyst, a hydrocarbon adsorbing material having the ability to adsorb and store hydrocarbons in the exhaust gas is used.
[0003] It is known that such exhaust gas purification catalysts are relatively inefficient in treating exhaust gas in a low temperature environment such as a cold start state of an internal combustion engine. Patent document 1 discloses a cold start catalyst, which contains: a zeolite catalyst containing a base metal, a noble metal and a zeolite; and a supported platinum group metal catalyst containing one or more platinum group metals and one or more inorganic oxide carriers in order to improve the exhaust gas purification efficiency in a cold start state. Patent document 1 discloses, for example, BEA type zeolite, MFI type zeolite, CHA type zeolite, etc. as the zeolite contained in the cold start catalyst.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application No. 2014-519975 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, the cold start catalyst disclosed in Patent Document 1 has the following problem: after hydrocarbons are stored in the cold start state, high-temperature exhaust gas flows in and the catalyst becomes hot, which causes the stored hydrocarbons to be desorbed before the catalyst is fully activated, so that the hydrocarbons are discharged without being purified. The hydrocarbon adsorbing material is required to have the following performance: it can adsorb and store hydrocarbons up to a temperature sufficient to activate the catalyst, and it can desorb the adsorbed and stored hydrocarbons at a temperature that activates the catalyst. In addition, since the exhaust gas purification catalyst is exposed to high-temperature exhaust gas, a hydrocarbon adsorbing material using zeolite with high heat resistance is also required.
[0009] Therefore, an object of the present invention is to provide a hydrocarbon adsorbing material, an exhaust gas purification catalyst, and an exhaust gas purification system, wherein the hydrocarbon adsorbing material adsorbs hydrocarbons, can store the adsorbed hydrocarbons until a relatively high temperature, can desorb the hydrocarbons at a relatively high temperature, and has excellent heat resistance.
[0010] Solutions for solving problems
[0011] The present invention provides a hydrocarbon adsorbent, which contains a porous zeolite containing a metal outside the zeolite framework, wherein the metal is at least one metal selected from the group consisting of transition metals belonging to Groups 3 to 12 in the periodic table, amphoteric metals belonging to Groups 13 and 14 in the periodic table, alkali metals and alkaline earth metals, and the content ratio of the metal relative to the porous zeolite containing the metal is 9% by mass or less.
[0012] The present invention provides an exhaust gas purification catalyst comprising: a substrate; a hydrocarbon adsorbing portion including the hydrocarbon adsorbing material on the substrate; and a purification catalyst portion on the hydrocarbon adsorbing portion.
[0013] The present invention provides an exhaust gas purification catalyst comprising: a substrate; a hydrocarbon adsorbing portion including the hydrocarbon adsorbing material and Rh on the substrate; and a purification catalyst portion including Pd on the hydrocarbon adsorbing portion.
[0014] The present invention provides an exhaust gas purification system, comprising: an internal combustion engine; a first exhaust gas purification catalyst arranged on the upstream side of an exhaust gas flow path connected to the internal combustion engine; and a second exhaust gas purification catalyst arranged on the downstream side of the exhaust gas flow direction compared with the first exhaust gas purification catalyst in the exhaust gas flow path, wherein the second exhaust gas purification catalyst is the aforementioned exhaust gas purification catalyst, and the content ratio of the platinum group metal in the second exhaust gas purification catalyst relative to the volume of the second exhaust gas purification catalyst is greater than 0.1 g / L and less than 3.0 g / L.
[0015] The present invention provides an exhaust gas purification system comprising: an internal combustion engine; and a single exhaust gas purification catalyst located in an exhaust gas flow path connected to the internal combustion engine, wherein the exhaust gas purification catalyst is the above-mentioned exhaust gas purification catalyst.
[0016] The present invention provides an exhaust gas purification system, comprising: an internal combustion engine; and a plurality of exhaust gas purification catalysts arranged in an exhaust gas flow path connected to the internal combustion engine, wherein, among the plurality of exhaust gas purification catalysts, the first exhaust gas purification catalyst arranged on the upstream side in the exhaust gas flow direction is the aforementioned exhaust gas purification catalyst.
[0017] The present invention provides a method for treating exhaust gas, which comprises the following steps: contacting a combustion exhaust gas containing hydrocarbons with the above-mentioned exhaust gas purification catalyst, adsorbing the hydrocarbons on the exhaust gas purification catalyst, and then desorbing the hydrocarbons from the exhaust gas purification catalyst at a temperature of 170°C or above. When water is contained in the combustion exhaust gas, the hydrocarbons are repeatedly adsorbed on the exhaust gas purification catalyst, desorbed, and re-adsorbed at a temperature of 200°C or below, so there is a tendency that the adsorption and desorption behavior of the hydrocarbons become complicated. Even in the case where water is contained in the combustion exhaust gas, if the temperature is 170°C or below, the hydrocarbons are adsorbed on the exhaust gas purification catalyst or desorbed, but are not adsorbed again on the exhaust gas purification catalyst. When the temperature is 170°C or below as a reference, even in the case where water is contained in the combustion exhaust gas, the re-adsorption of the hydrocarbons on the exhaust gas purification catalyst is not considered, and the adsorption or desorption of the hydrocarbons on the exhaust gas purification catalyst can be evaluated. The present invention provides a method for treating exhaust gas, which can adsorb and store hydrocarbons until activation, and can desorb the adsorbed hydrocarbons after activation to purify.
[0018] Effects of the Invention
[0019] The hydrocarbon adsorbent provided by the present invention contains a porous zeolite containing a specific metal outside the zeolite framework, and can adsorb and store hydrocarbons up to a relatively high temperature, and can desorb the stored hydrocarbons at a high temperature of, for example, 170° C. or higher. In addition, the hydrocarbon adsorbent is also excellent in heat resistance, and in an exhaust gas purification catalyst using the hydrocarbon adsorbent and an exhaust gas purification system including the exhaust gas purification catalyst, the hydrocarbon removal performance can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic perspective view showing an exhaust gas purification catalyst.
[0021] Figure 2 It is an enlarged view of a part of the cross section showing a first example of the exhaust gas purification catalyst.
[0022] Figure 3 It is an enlarged view of a part of the cross section showing a second example of the exhaust gas purification catalyst.
[0023] Figure 4 1 is a schematic structural diagram showing a first example of an exhaust gas purification system.
[0024] Figure 5 1 is a schematic structural diagram showing a second example of the exhaust gas purification system.
[0025] Figure 6 1 is a schematic structural diagram showing a third example of the exhaust gas purification system.
[0026] Figure 7 The X-ray diffraction spectrum of the obtained MSE type zeolite is shown.
[0027] Figure 8 The X-ray diffraction spectrum of the obtained EON type zeolite is shown. DETAILED DESCRIPTION
[0028] Next, the present invention will be described based on examples of embodiments. It should be noted that the present invention is not limited to the embodiments described below.
[0029] As an example of an embodiment of the present invention, a porous zeolite containing at least one metal selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals outside the zeolite framework, wherein the content ratio of the metal to the porous zeolite containing the metal is 9% by mass or less. A porous zeolite containing at least one metal selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals outside the zeolite framework as a hydrocarbon adsorbent can adsorb hydrocarbons at a relatively low temperature of, for example, about 50°C, store hydrocarbons at a relatively high temperature of, for example, up to 200°C, and desorb the stored hydrocarbons at a relatively high temperature of, for example, more than 200°C. Furthermore, when the exhaust gas contains water, hydrocarbons can be stored at a relatively high temperature up to 170°C at which the adsorption and desorption of hydrocarbons can be evaluated without considering the re-adsorption during the adsorption, desorption and re-adsorption of hydrocarbons by the hydrocarbon adsorbing material, and the stored hydrocarbons can be desorbed at a temperature exceeding 170°C.
[0030] Zeolite has a crystal structure of a crystalline or quasicrystalline aluminosilicate consisting of repeating units of SiO4 and AlO4 tetrahedra. The units forming the framework structure of zeolite are sometimes written as TO4 units. The framework structure of zeolite is given a structure code of three uppercase Arabic characters defined in the International Zeolite Association. The structure can be confirmed by a database provided by the Structure Commission of the International Zeolite Association (Databese of Zeolite Structures, Structure Commission of the International Zeolite Association).
[0031] Porous zeolite is a zeolite having a variety of pore structures of different sizes. The porous zeolite used in the embodiment of the present invention can be listed as a zeolite containing large-pore tunnel-type pores and small-pore cages as the pore structure. Tunnel-type pores are sometimes also called linear pores, and in this specification, they are sometimes written as "tunnel-type (linear) pores". In addition, the porous zeolite may further contain large-pore cages. As large-pore tunnel-type (linear) pores, tunnel-type (linear) pores with a maximum of twelve-membered rings and tunnel-type (linear) pores with a maximum of ten-membered rings, etc., which have a ring of more than ten-membered rings, can be listed. As large-pore cages, cages with a maximum of ten-membered rings, etc., which have a ring of more than ten-membered rings, can be listed. As small-pore cages, cages with a maximum of eight-membered rings and cages with a maximum of six-membered rings, etc., which have a maximum ring of less than eight-membered rings, can be listed. As porous zeolites used in the embodiment of the present invention, for example, MSE zeolites having tunnel-type (linear) pores with a maximum of twelve-membered rings, cages with a maximum of ten-membered rings, and cages with a maximum of six-membered rings (cages composed of six-membered rings and four-membered rings), EON zeolites having tunnel-type (linear) pores with a maximum of twelve-membered rings and cages with a maximum of eight-membered rings (cages composed of eight-membered rings, six-membered rings, and four-membered rings), and MOR zeolites having tunnel-type (linear) pores with a maximum of twelve-membered rings and cages with a maximum of eight-membered rings. Among them, MSE zeolites having tunnel-type (linear) pores with a maximum of twelve-membered rings, cages with a maximum of ten-membered rings, and cages with a maximum of six-membered rings and EON zeolites having tunnel-type (linear) pores with a maximum of twelve-membered rings and cages with a maximum of eight-membered rings are preferred, and MSE zeolites are particularly preferred. It should be noted that BEA zeolite having only tunnel-type (linear) pores with a maximum of twelve-membered rings and MFI zeolite having only tunnel-type (linear) pores with a maximum of ten-membered rings are not porous zeolites because they have only one type of pore structure.
[0032] MSE zeolite has a tunnel type (straight type) with a maximum of twelve-membered rings, a cage hole with a maximum of ten-membered rings, and a cage with a maximum of six-membered rings (a cage composed of six-membered rings and four-membered rings). The crystal structure of a typical MSE zeolite belongs to the tetragonal system (tetragonal) and the P42 / mnm space group. It should be noted that sometimes the space group changes when the MSE zeolite is modified by metal ions. In addition, in a typical MSE zeolite, the lattice constant a, which represents the length of the axis of the unit cell, is 18.2461 angstroms. The lattice constant b is 18.2461 angstroms The lattice constant c is 20.5569 angstroms The angles α, β, and γ indicating the angles between the axes of the unit cell are 90 degrees respectively (α=90.000°, β=90.000°, γ=90.000°). The crystal structure of zeolite can be found in the database of Zeolite Structures, Structure Commission of the International Zeolite Association.
[0033] EON zeolite has a tunnel-type (linear) hole with a maximum of twelve-membered rings and a cage with a maximum of eight-membered rings (a cage composed of eight-membered rings, six-membered rings and four-membered rings). The crystal structure of a typical EON zeolite belongs to the orthorhombic system and the Pmmn space group. It should be noted that sometimes the space group changes when the EON zeolite is modified by metal ions. In addition, in a typical EON zeolite, the lattice constant a representing the length of the axis of the unit cell is 7.5709 angstroms. The lattice constant b is 18.1480 angstroms The lattice constant c is 25.9324 angstroms α, β, and γ indicating the angles between the axes of the unit cell are each 90 degrees (α=90.000°, β=90.000°, γ=90.000°).
[0034] The SiO2 / Al2O3 molar ratio of the porous zeolite is preferably 10 or more and 600 or less. The SiO2 / Al2O3 molar ratio of the porous zeolite may be 12 or more, 15 or more, 18 or more, 20 or more, 500 or less, 400 or less, 300 or less, or 250 or less. The SiO2 / Al2O3 molar ratio of the porous zeolite is more preferably 12 or more and 500 or less, further preferably in the range of 13 or more and 400 or less, and particularly preferably in the range of 15 or more and 250 or less. When the SiO2 / Al2O3 molar ratio of the porous zeolite is 10 or more, the crystal structure is stable and has excellent heat resistance. In addition, when the SiO2 / Al2O3 molar ratio of the porous zeolite is less than 600, at least one metal ion selected from the group consisting of transition metals belonging to Groups 3 to 12 in the periodic table, amphoteric metals belonging to Groups 13 and 14 in the periodic table, alkali metals and alkaline earth metals is easily exchanged with the group ion of the oxygen atom adjacent to the Al atom of the porous zeolite to become the Bronsted acid center, so that the above-mentioned metal ion is contained outside the zeolite framework. The SiO2 / Al2O3 molar ratio contained in the porous zeolite or the hydrocarbon adsorbent described later is measured by elemental analysis using, for example, a scanning fluorescent X-ray analyzer (ZSX Primus II, manufactured by Rigaku Co., Ltd.) to measure the Si amount and Al amount, and the SiO2 / Al2O3 molar ratio can be measured based on the obtained Si amount and Al amount.
[0035] As an example of an embodiment of the present invention, the porous zeolite contains at least one metal selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals and alkaline earth metals outside the zeolite framework. Preferably, the metal is introduced by ion exchange of the porous zeolite, but the porous zeolite may be modified in the form of an oxide. The metal introduced by ion exchange and the metal modified in the form of an oxide may also be mixed. When the porous zeolite is ion-exchanged with the ions of the metal, the cations present in the pores of the porous zeolite act as acid centers and can chemically adsorb hydrocarbons. By exchanging metal ions on the porous zeolite exchanged with alkaline ammonium ions, protons (H +) is suppressed to a minimum, and by performing ion exchange of the porous zeolite at a high pH of pH 4 or higher, the generation of hydroxyl groups in the zeolite framework can be suppressed, so that the porous zeolite can preferentially adsorb hydrocarbons at a relatively low temperature, such as around 50°C, and store hydrocarbons at a relatively high temperature, such as 200°C or higher, and can desorb hydrocarbons at a relatively high temperature, such as more than 200°C. In addition, in the case where the exhaust gas contains moisture, the porous zeolite contains at least one metal selected from the group consisting of transition metals belonging to Groups 3 to 12 in the periodic table, amphoteric metals belonging to Groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals outside the zeolite framework, so that the porous zeolite can store hydrocarbons at a relatively high temperature of 170°C, at which the adsorption and desorption of hydrocarbons can be evaluated without considering the re-adsorption in the adsorption, desorption and re-adsorption of hydrocarbons, and can desorb the stored hydrocarbons at a temperature exceeding 170°C.
[0036] The ion exchange sites in the zeolite pores of the porous zeolite are sometimes selected from at least one metal ion exchange in the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals. "Ion exchange sites in the zeolite pores" specifically refers to a group of oxygen atoms that are adjacent to Al atoms that are part of the T site constituting the skeleton and serve as Bronsted acid centers. That is, the porous zeolite performs ion exchange at the Bronsted acid centers of the repeating units of SiO4 and AlO4 tetrahedrons that constitute the skeleton of the zeolite, thereby containing specific metals outside the zeolite skeleton. By performing metal ion exchange at the ion exchange sites of the porous zeolite and making the metal present outside the zeolite skeleton, hydrocarbons are preferentially adsorbed, which can improve the adsorption capacity of hydrocarbons.
[0037] The content ratio of at least one metal selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals and alkaline earth metals contained outside the zeolite framework of the porous zeolite is 9% by mass or less, preferably 8% by mass or less, more preferably 7% by mass or less, relative to the porous zeolite containing the metal, and can be 1% by mass or more, preferably 1.2% by mass or more, and more preferably 1.5% by mass or more. When the content ratio of the specific metal contained in the porous zeolite is 9% by mass or less, the heat resistance of the porous zeolite containing the metal can be suppressed from decreasing. In particular, by introducing a specific metal in a manner that replaces Si in the porous zeolite framework, the content of the metal increases, and thus the heat resistance of the porous zeolite is easily reduced, so it is not preferred. In the case where a plurality of specific metals are contained in the porous zeolite, the content ratio of the metal refers to the sum of the plurality of specific metals.
[0038] The transition metals belonging to Groups 3 to 12 in the periodic table contained in the porous zeolite may include at least one element selected from the group consisting of iron (Fe), palladium (Pd), rhodium (Rh), platinum (Pt), manganese (Mn), nickel (Ni), zinc (Zn), silver (Ag), copper (Cu), titanium (Ti), vanadium (V), chromium (Cr), cobalt (Co), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc) and ruthenium (Ru). In this specification, the metals belonging to Group 12 in the periodic table are also considered to be included in the transition metals. The amphoteric metals belonging to Groups 13 and 14 in the periodic table contained in the porous zeolite may include at least one element selected from the group consisting of aluminum (Al), gallium (Ga), indium (In), thallium (Tl), germanium (Ge), tin (Sn) and lead (Pb). The amphoteric metal belonging to the 13th and 14th groups in the periodic table contained outside the zeolite framework may not contain aluminum (Al), and the amphoteric metal belonging to the 13th and 14th groups in the periodic table contained outside the zeolite framework may be at least one element selected from the group consisting of gallium (Ga), indium (In), thallium (Tl), germanium (Ge), tin (Sn) and lead (Pb). The alkali metal contained in the porous zeolite is preferably an ion of at least one selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs). The alkaline earth metal contained in the porous zeolite is preferably at least one selected from the group consisting of calcium (Ca), strontium (Sr) and barium (Ba). The metal contained in the porous zeolite may be at least one selected from the group consisting of Fe, Pd, Rh, Pt, Mn, Ni, Zn, Ag, Cu, Ti, V, Cr, Co, Zr, Nb, Mo, Tc, Ru, Al, Ga, In, Tl, Ge, Sn, Pb, Li, Na, K, Rb, Cs, Ca, Sr and Ba. In addition, the porous zeolite may contain magnesium (Mg).
[0039] The metal contained outside the zeolite framework of the porous zeolite is more preferably at least one selected from the group consisting of Mn, Fe, Ni, Cu, Zn, Ga, Rh, Pd, Ag, Sn, Sc and Pt. The porous zeolite is exchanged with at least one metal ion selected from the group consisting of Mn, Fe, Ni, Cu, Zn, Ga, Rh, Pd, Ag, Sn, Sc and Pt through the ion exchange site, and the hydrocarbon stably adsorbed in the pore is chemically adsorbed to the metal so that it can be further stably present in the pore, so that the hydrocarbon can be stored until a higher temperature. The ion exchange site of the porous zeolite can also be exchanged with hydrogen ions in addition to metal ions.
[0040] The porous zeolite contains one metal selected from the group consisting of transition metals belonging to Groups 3 to 12 in the periodic table, amphoteric metals belonging to Groups 13 and 14 in the periodic table, alkali metals and alkaline earth metals outside the zeolite framework, preferably containing the above metal in a manner such that the molar ratio of the metal contained outside the zeolite framework to Al, i.e., the metal / Al ratio, is in the range of 0.01 or more and 2.5 or less, and in the case of containing a plurality of metal species (M x1 、M x2 , ···), preferably each metal (M x1、 M x2、 The sum of the molar ratios of ···) and Al (M x1 / Al+M x2 / Al+···) is in the range of 0.01 to 2.5, including a variety of metal types. When the molar ratio of the metal contained outside the zeolite framework of the porous zeolite to Al, that is, the metal / Al ratio, is in the range of 0.01 to 2.5, the zeolite structure has stability, so it is preferred. When the molar ratio of the metal contained outside the zeolite framework of the porous zeolite to Al, that is, the metal / Al ratio, is in the range of 0.05 to 2.5, the adsorption performance of hydrocarbons (HC) is excellent, so it is more preferred. The amount of elements M and Al contained in the porous zeolite or the exhaust gas purification composition described later can be measured by elemental analysis, for example, using a scanning fluorescent X-ray analyzer (ZSX Primus II, manufactured by Rigaku Co., Ltd.).
[0041] The porous zeolite may contain phosphorus or sulfur, preferably phosphorus. When phosphorus or sulfur is contained in the porous zeolite, the part that causes the defect of the skeleton structure is easily modified by phosphorus or sulfur. When the part that causes the defect of the skeleton structure is modified by phosphorus or sulfur, the skeleton structure of the porous zeolite can be maintained even when placed in a harsh thermal environment, thereby improving heat resistance. The phosphorus or sulfur produced by the phosphorus source or sulfur source becomes in the form of, for example, phosphate ions or sulfate ions, so that it is easier to bind to the Lewis acid center where the metal ion is located than the Bronsted acid center. In the porous zeolite, the Bronsted acid center that becomes the active point for the oxidation of adsorbed hydrocarbons (HC) is maintained, and the phosphate ions or sulfate ions, etc., are combined with the metal ions that cause the defect of the skeleton structure to maintain the skeleton structure. Therefore, while maintaining the purification performance of hydrocarbons, the skeleton structure can be maintained even when placed in a harsh thermal environment to improve heat resistance.
[0042] In the case where the porous zeolite contains phosphorus, the molar ratio of aluminum to phosphorus, i.e., the P / Al molar ratio, of the porous zeolite containing phosphorus is preferably within the range of 0.4 to 1.1. The P / Al molar ratio is more preferably within the range of 0.8 to 1.0. When the molar ratio of Al to phosphorus (P) of the T atom (central atom) of the TO4 unit forming the skeleton structure of the porous zeolite, i.e., the P / Al molar ratio, is within the range of 0.4 to 1.1, the phosphorus contained in the porous zeolite is modified to the Lewis acid center formed by Al, and the Bronsted acid center, which becomes the active point for oxidation of the adsorbed hydrocarbon (HC), is maintained. Therefore, while maintaining the purification performance, the defects of the skeleton structure are suppressed, and the skeleton structure can be maintained even in a harsh thermal environment, further improving the heat resistance. When the P / Al molar ratio in the porous zeolite containing phosphorus is within the range of 0.4 to 1.1, the defects of the skeleton structure can be suppressed, and the adsorption performance and purification performance of hydrocarbons can be maintained. As described in the examples below, the amount of aluminum (Al) and phosphorus (P) in the porous zeolite containing phosphorus is measured using a scanning fluorescent X-ray analyzer (e.g., manufactured by Rigaku Co., Ltd.), and the amount of aluminum (Al) and phosphorus (P) in the porous zeolite containing phosphorus can be calculated from the measured values.
[0043] The BET specific surface area A of the porous zeolite is preferably 400 m 2 / g and above 1000m 2 The BET specific surface area of the porous zeolite is 400 m 2 / g and above 1000m 2 When the porous zeolite has a BET specific surface area of 450 m / g or less, the amount of hydrocarbon adsorbed per unit weight of the porous zeolite is large, and thus the hydrocarbon (HC) adsorption performance is excellent. 2 In order to maintain the framework structure even when placed in a severe thermal environment, the BET specific surface area of the porous zeolite is preferably 800 m 2 / g or less, can be 700m 2 / g or less, and can also be 600m 2 / g or less.
[0044] The ratio B / A of the BET specific surface area A of the porous zeolite before heat treatment to the BET specific surface area B of the porous zeolite after heat treatment satisfying the heat treatment conditions of (1) to (5) below is preferably within the range of 0.35 or more and 1 or less. When the ratio B / A of the BET specific surface area A of the porous zeolite before heat treatment to the BET specific surface area B of the porous zeolite after heat treatment is 1, it means that the structure of the porous zeolite does not change before and after heat treatment, and the structure is maintained. When the ratio B / A of the BET specific surface area of the porous zeolite before and after heat treatment is within the range of 0.35 or more and 1 or less, the microporous structure is relatively maintained even when placed in a harsh thermal environment, so it is preferred. The ratio B / A of the specific surface area of the porous zeolite before and after heat treatment is more preferably within the range of 0.4 or more and 1 or less, further preferably within the range of 0.3 or more and 1 or less, further preferably within the range of 0.5 or more and 1 or less, and particularly preferably within the range of 0.5 or more and 0.9 or less.
[0045] Heat treatment conditions
[0046] (1) Temperature: 850°C
[0047] (2) Duration: 25 hours
[0048] (3) Atmosphere: An atmosphere containing 10% by volume of water vapor (H2O), wherein water vapor is vaporized from a tank containing water and the saturated water vapor pressure is adjusted by temperature to produce an atmosphere containing 10% by volume of water vapor.
[0049] (4) Sample gas (model gas) flow mode: The sample gas (5) described below is flowed at 3 L / min for 80 seconds and the air is flowed at 3 L / min for 20 seconds alternately.
[0050] (5) Sample gas: The sum of C3H6, O2 and N2 is 3 L / min, C3H6 is 70 mL / min, O2 is 70 mL / min, and the balance is N2.
[0051] In the porous zeolite, the MSE type zeolite has a diffraction peak at a diffraction angle position of 21.7°±1.0° representing the diffraction index (420) in the X-ray diffraction spectrum of the MSE type zeolite, and the ratio D / C of the peak intensity C of the diffraction index (420) before heat treatment to the peak intensity D of the diffraction index (420) after heat treatment satisfying the heat treatment conditions of the above (1) to (5) is preferably in the range of 0.3 or more and 1.5 or less. In the X-ray diffraction spectrum of the MSE type zeolite, when the peak intensity ratio D / C of the peak intensity C before heat treatment appearing at the diffraction angle (2θ) position of 21.7°±1.0° representing the diffraction index (420) before heat treatment to the peak intensity D after heat treatment is in the range of 0.3 or more and 1.5 or less, the skeleton structure is maintained even when placed in a severe thermal environment, and therefore it is preferred. The peak intensity ratio D / C is more preferably in the range of 0.4 to 1.4, further preferably in the range of 0.5 to 1.3, and further preferably in the range of 0.6 to 1.2. The X-ray diffraction spectrum of the MSE zeolite can be measured using an X-ray diffraction device (e.g., model: MiniFlex600, manufactured by Rigaku Co., Ltd.).
[0052] Method for producing MSE type zeolite
[0053] The MSE type zeolite comprises a step of preparing a raw material mixture containing a silica source, an aluminum source, an alkali metal source, an organic structure directing agent (template), and water; and a step of heating the raw material mixture to crystallize the mixture to obtain the MSE type zeolite.
[0054] The silica source can use, for example, a compound containing silicon. Specifically, wet-process silica, dry-process silica, colloidal silica, sodium silicate, potassium silicate, aluminum silicate gel, etc. can be cited. These silica sources can be used alone or in combination of two or more. Among these silica sources, silica (silicon dioxide), aluminum silicate gel, and colloidal silica are preferably used because they are difficult to generate by-products and can produce the target MSE type zeolite.
[0055] The aluminum source may be, for example, a water-soluble aluminum-containing compound. Specifically, sodium aluminate, aluminum nitrate, aluminum sulfate, aluminum hydroxide, aluminum silicate gel, etc. may be cited. These aluminum sources may be used alone or in combination of two or more. Of these aluminum sources, sodium aluminate or aluminum silicate gel is preferably used because it is difficult to generate by-products and the target MSE type zeolite can be produced.
[0056] As the alkali metal source, for example, cesium hydroxide, potassium hydroxide, and sodium hydroxide can be used. It should be noted that when sodium silicate is used as the silica source and sodium aluminate is used as the aluminum source, the sodium contained therein as the alkali metal component is also an alkali metal component. The alkali metal source is calculated as the sum of all alkali metal components in the reaction mixture.
[0057] The organic structure directing agent may include an organic structure directing agent containing N,N,N',N'-tetraalkylbicyclo[2.2.2]oct-7-ene-2,3:5,6-dipyrrolidinium ion. The organic structure directing agent may be N,N,N',N'-tetraalkylbicyclo[2.2.2]oct-7-ene-2,3:5,6-dipyrrolidinium iodide, and the alkyl groups may be the same or different.
[0058] Process of preparing raw material mixture
[0059] When preparing the raw material mixture, the order of adding the raw materials can be a method that can easily obtain a uniformly mixed raw material mixture. For example, at room temperature, by adding an aluminum source to an alkali metal source that acts as a mineralizer to dissolve it, and then adding a silica source to stir and mix, a uniformly mixed raw material mixture can be obtained. The temperature when preparing the raw material mixture can generally be prepared at room temperature (20°C to 25°C).
[0060] The crystallization process
[0061] The raw material mixture can be heated at a temperature of 70°C to 240°C to crystallize. The heating of the raw material mixture is also referred to as the first heating. The first heating can be performed while the raw material mixture is left to stand, or while stirring the raw material mixture. The heating temperature can be a temperature of 80°C to 200°C. The heating time can be 5 hours to 400 hours, 48 hours to 200 hours, or 72 hours to 80 hours. The heating can be performed under atmospheric pressure or under pressure.
[0062] The raw material mixture may be aged by standing at a temperature lower than the heating temperature for a certain period of time before heating. Aging means keeping the reaction mixture at a temperature lower than the heating temperature for crystallization for a certain period of time. The aging temperature may be a temperature above room temperature (20° C. to 25° C.) and below 160° C., and the aging time may be 2 hours or more and within 160 hours.
[0063] After heating, the crystallized powder is separated from the mother liquor by filtration, and washed and dried with water or deionized water to obtain MSE zeolite. The obtained MSE zeolite is heated to remove organic matter remaining in the crystals. Heating to remove organic matter remaining in the crystals is also referred to as the second heating. The second heating can be performed at a temperature that can remove the organic matter, preferably in a range of 500°C to 800°C. In addition, in order to maintain the skeleton structure of the obtained MSE zeolite, it is preferably taken more than 2 hours to heat up to the heating temperature, and the heating time for maintaining the heating temperature after heating to the heating temperature is preferably more than 0.5 hours and less than 3 hours.
[0064] The obtained MSE zeolite can be confirmed as MSE zeolite by measuring using a powder X-ray diffractometer. In the X-ray diffraction spectrum using the powder X-ray diffractometer, if there are diffraction peaks at diffraction angles (2θ) of 6.56±0.15°, 6.8±0.15°, 8.04±0.15°, 19.38±0.15°, 19.42±0.15°, 21.68±0.15°, 22.28±0.15°, 22.32±0.15°, 22.84±0.15°, and 27.5°±0.15°, it can be confirmed as MSE zeolite.
[0065] Method for producing EON type zeolite
[0066] The EON type zeolite comprises the steps of preparing a raw material mixture containing a silica source, an aluminum source, an alkali metal source, water, and, if necessary, an organic structure directing agent (template); and heating the raw material mixture to crystallize the mixture to obtain the EON type zeolite.
[0067] As the silica source, the aluminum source, and the alkali metal source, the same raw materials as those used in the above-mentioned method for producing the MSE-type zeolite can be used.
[0068] Examples of the organic structure directing agent include an organic structure directing agent containing bis(2-hydroxyethyl)dimethylammonium ion and tris(2-hydroxyethyl)methylammonium. The organic structure directing agent may be bis(2-hydroxyethyl)dimethylammonium chloride or tris(2-hydroxyethyl)methylammonium hydroxide.
[0069] Process of preparing raw material mixture
[0070] The raw material mixture can be prepared in the same manner as in the above-mentioned method for producing the MSE type zeolite.
[0071] The crystallization process
[0072] The raw material mixture can be heated at a temperature of 70°C to 240°C to crystallize. The heating of the raw material mixture is also referred to as the first heating. The first heating can be performed while the raw material mixture is left to stand, or while stirring the raw material mixture. The heating temperature can be a temperature of 80°C to 200°C. The heating time can be 24 hours to 400 hours, 48 hours to 200 hours, or 72 hours to 170 hours. The heating can be performed under atmospheric pressure or under pressure.
[0073] The raw material mixture may be aged by standing at a temperature lower than the heating temperature for a certain period of time before heating. Aging means keeping the reaction mixture at a temperature lower than the heating temperature for crystallization for a certain period of time. The aging temperature may be a temperature above room temperature (20° C. to 25° C.) and below 80° C., and the aging time may be 2 hours or more and within 80 hours.
[0074] After heating, the crystallized powder is separated from the mother liquor by filtration, and washed and dried with water or deionized water to obtain EON-type zeolite. When an organic structure directing agent is used for synthesis, the EON-type zeolite is heated to remove the organic matter remaining in the crystals. The heating to remove the organic matter remaining in the crystals is also referred to as the second heating. The second heating can be any temperature that can remove the organic matter, and is preferably carried out in a range of 500°C to 800°C. In addition, in order to maintain the skeleton structure of the obtained EON-type zeolite, it is preferably taken more than 2 hours to heat up to the heating temperature, and the heating time for maintaining the heating temperature after heating to the heating temperature is preferably more than 0.5 hours and less than 3 hours.
[0075] The obtained EON type zeolite can be confirmed as EON type zeolite by measuring using a powder X-ray diffractometer. In the X-ray diffraction spectrum using the powder X-ray diffractometer, if there is a diffraction peak at the diffraction angle (2θ) position of 6.42±0.14°, 9.66±0.15°, 13.02±0.15°, 13.38±0.15°, 23.12±0.15°, 25.44±0.15°, 26.18±0.15°, 27.56±0.15°, 27.78±0.16°, 28.06±0.17°, it can be confirmed as EON type zeolite.
[0076] Method for making porous zeolite contain metal
[0077] Porous zeolite can be made to contain metal by liquid phase ion exchange method, solid phase ion exchange method, and impregnation method. As a method of containing metal, a method of introducing metal into porous zeolite by ion exchange, a method of modifying the surface of porous zeolite in a state of belonging to oxide, etc. can be cited. The liquid phase ion exchange method is a method of dispersing or impregnating porous zeolite in a solution of a metal salt composed of at least one metal ion selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals to perform ion exchange. The solid phase ion exchange method is a method of performing ion exchange by mixing porous zeolite with a metal salt or metal oxide containing at least one metal ion selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals, and heat treating at a temperature of, for example, 300°C or more and 800°C or less in a reducing atmosphere or an inactive atmosphere. As the types of metal salts, for example, metal acetate, metal chloride, metal sulfate, metal nitrate, etc. can be cited. After the ion exchange treatment, the ion-exchanged porous zeolite is washed, dried at, for example, 100°C to 300°C, and then calcined at, for example, 400°C to 1000°C to obtain a porous zeolite in which the ion exchange site on Al is ion-exchanged. The impregnation method is to immerse the porous zeolite in a solution of a metal salt or metal oxide containing at least one metal ion selected from the group consisting of transition metals belonging to groups 3 to 12 in the periodic table, amphoteric metals belonging to groups 13 and 14 in the periodic table, alkali metals, and alkaline earth metals, and heat-treat it at a temperature of, for example, 30°C or more and 200°C or less to dry it, thereby containing a metal. After drying, calcination is performed at, for example, 400°C to 1000°C to obtain a porous zeolite in which the ion exchange site on Al is ion-exchanged. As the type of metal salt, for example, metal acetate, metal chloride, metal sulfate, metal nitrate, etc. can be cited. As the impregnation method, equal volume impregnation (incipientwetness) method, evaporation drying method, pore filling (pore-filling) method, spray method, equilibrium adsorption method, etc. can be listed. As the precipitation method, mixing method, deposition method, etc. can be listed. At least a portion of the specific metal introduced into the porous zeolite is preferably introduced into a cage of small pores (a cage with a maximum ring of less than eight-membered rings), and it is particularly preferred to introduce a cage of a maximum eight-membered ring or a cage of a maximum six-membered ring. In order to introduce the specific metal into the cage of the small pores, the calcination temperature is preferably above 450°C, and it can also be calcined in an air atmosphere, and it is ideal to calcine in an inactive atmosphere or under a reduced pressure of less than 0.1MPa.By introducing the metal into the small-pore cage, the volume of the large pores (pores with rings of ten or more members) for adsorbing hydrocarbons, especially the volume of the tunnel-type (linear) pores with a maximum of twelve-membered rings and the cage-type pores with a maximum of ten-membered rings, can be maintained. In addition, the specific metal does not directly react with the hydrocarbons, but the specific metal acts on the zeolite framework, so the porous zeolite containing the specific metal can adsorb hydrocarbons up to high temperatures.
[0078] The specific metal introduced into the cage of the small hole of porous zeolite can be indirectly confirmed by the change of the lattice constant of zeolite by the determination of X-ray diffraction. In addition, in porous zeolite, relative to the content of the specific metal introduced into the tunnel type (linear) hole of the maximum twelve-membered ring and the cage type hole of the maximum ten-membered ring, the content of the specific metal introduced into the cage of the small hole is preferably greater than 0.5 in molar ratio, more preferably more than 1.0, further preferably more than 2.0, especially preferably more than 3.0. The content of the specific metal in the tunnel type (linear) hole of the maximum twelve-membered ring, the cage type hole of the maximum ten-membered ring or the cage of the small hole can be obtained according to the change of the TO bonding distance of the TO4 unit that forms the skeleton structure, the distance from the skeleton element obtained by using X-ray diffraction device etc.
[0079] Method for making porous zeolite contain phosphorus or sulfur
[0080] Porous zeolite is contacted with a compound containing phosphorus or a compound containing sulfur, so that the porous zeolite can contain phosphorus or sulfur. As a method for making porous zeolite contain phosphorus or sulfur, evaporation method, impregnation method, precipitation method, ion exchange method, etc. can be listed. As an evaporation method, porous zeolite and a compound containing phosphorus or a compound containing sulfur are placed in a container, and phosphorus or sulfur is evaporated at room temperature or heated, so that the porous zeolite contains phosphorus or sulfur. As an impregnation method, porous zeolite can be immersed in a liquid mixed with a compound containing phosphorus or a compound containing sulfur and a solvent, and the mixed solution is heated and dried under normal pressure or reduced pressure to make the porous zeolite contain phosphorus or sulfur. Here, the compound containing phosphorus can be phosphorus, or it can be an ion containing phosphorus. In addition, the compound containing sulfur can be sulfur, or it can be an ion containing sulfur. As an impregnation method, isovolumetric impregnation (incipientwetness) method, evaporation and drying method, pore filling (pore-filling) method, spray method, equilibrium adsorption method, etc. can be listed. Examples of the precipitation method include a kneading method and a sedimentation method.
[0081] When the porous zeolite is made to contain phosphorus by a vapor deposition method, examples of the compound containing phosphorus include trimethyl phosphate, triethyl phosphate, trimethyl phosphite, triethyl phosphite, etc. In view of the low boiling point, trimethyl phosphate is preferred. When the porous zeolite is made to contain phosphorus by an impregnation method, the compound containing phosphorus is preferably water-soluble, and examples thereof include trimethyl phosphate, triethyl phosphate, trimethyl phosphite, triethyl phosphite, phosphoric acid, diammonium dihydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate and other dihydrogen phosphates, diammonium hydrogen phosphate, dipotassium hydrogen phosphate and other hydrogen phosphates. Examples of phosphoric acid include orthophosphoric acid (H3PO4), pyrophosphoric acid (H4P2O7), triphosphoric acid (H5P3O 10 ), polyphosphoric acid, metaphosphoric acid (HPO3), superphosphoric acid, etc. From the perspective of easy drying, phosphoric acid such as orthophosphoric acid, trimethyl phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate are preferred. As solvents mixed with compounds containing phosphorus, polar organic solvents such as deionized water, ethanol, 2-propanol, acetone, etc. can be listed. From the perspective of easy operation and easy drying, deionized water and ethanol are preferably used. Relative to the total amount of the mixed solution of 100 mass%, the compound containing phosphorus can be in the range of more than 1 mass% and less than 25 mass%, or in the range of more than 2 mass% and less than 20 mass%, or in the range of more than 5 mass% and less than 15 mass%. In the case where the compound containing phosphorus is attached to the porous zeolite by an impregnation method, the time for the porous zeolite to be immersed in the mixed solution can be set to more than 0.5 hours and less than 2 hours. After impregnation, the porous zeolite containing the compound containing phosphorus can be dried, the drying temperature can be set to more than 80°C and less than 200°C, and the drying time can be set to more than 0.5 hours and less than 5 hours. The pressure during drying is not particularly limited, and may be atmospheric pressure (0.1 MPa) or reduced pressure of 0.1 MPa or less. When sulfur is added to the porous zeolite, it is preferred to use sulfate.
[0082] After a compound containing phosphorus or sulfur is attached to a porous zeolite by a vapor deposition method or an impregnation method, a thermal treatment is performed to obtain a porous zeolite containing phosphorus or sulfur. In order to maintain the skeleton structure of the porous zeolite, the thermal treatment temperature is preferably in the range of 200°C to 800°C, more preferably in the range of 400°C to 700°C. The atmosphere for the thermal treatment may be an air atmosphere, an inert gas atmosphere such as nitrogen, etc.
[0083] A porous zeolite containing a specific metal can be used as a hydrocarbon adsorbent. In the exhaust gas purification catalyst described later, the hydrocarbon adsorbent constituting the hydrocarbon adsorption portion may further include non-porous zeolites such as BEA type (zeolite with only twelve-membered rings) and MTW type (zeolite with only twelve-membered rings) in addition to the porous zeolite containing the specific metal. For example, the MSE type zeolite as a porous zeolite includes a case where it includes MOR type zeolite as a porous zeolite, BEA type zeolite as a non-porous zeolite, and MTW type zeolite as a non-porous zeolite. The hydrocarbon adsorbent may be composed of 100 mass % of a porous zeolite containing a specific metal. In the case where the porous zeolite containing the specific metal also includes non-porous zeolites such as BEA type and MTW type, the content of the porous zeolite containing the specific metal in 100 mass % of the hydrocarbon adsorbent is preferably in the range of 50 mass % to 99 mass %, more preferably in the range of 80 mass % to 99 mass %, and further preferably in the range of 90 mass % to 99 mass %.
[0084] A hydrocarbon adsorbing material composed of a porous zeolite containing a specific metal element can be used as an exhaust gas purification catalyst by combining a hydrocarbon adsorbing portion containing the hydrocarbon adsorbing material with a purification catalyst portion. A hydrocarbon adsorbing material composed of a porous zeolite containing a specific metal element can be used to manufacture a hydrocarbon adsorbing portion composition containing the hydrocarbon adsorbing material to form a hydrocarbon adsorbing portion.
[0085] Exhaust gas purification catalyst
[0086] A first example of an embodiment of the present invention is an exhaust gas purification catalyst including: a substrate; a hydrocarbon adsorbing portion including the hydrocarbon adsorbing material on the substrate; and a purification catalyst portion on the hydrocarbon adsorbing portion.
[0087] Figure 1 and Figure 2 One example of the exhaust gas purification catalyst 10 is shown. Figure 1 A ceramic substrate 1 is shown, and the substrate 1 has a plurality of cavities 1 a and partition walls 1 b that partition the cavities 1 a . Figure 2 FIG. 1 shows a part of a cross section of an exhaust gas purification catalyst according to a first example. The exhaust gas purification catalyst 10 includes: a substrate 1; a hydrocarbon adsorbing portion 2 provided on the substrate 1; and a purification catalyst portion 3 on the hydrocarbon adsorbing portion 2. Figure 2 In the figure, reference numeral 30 denotes an exhaust gas flow path.
[0088] The purification catalyst section 3 of the first example comprises: a first purification catalyst section 3a comprising at least one of Rh and Pt, with a Pd content of less than 0.1% by mass; and a second purification catalyst section 3b comprising at least one of Pd and Pt, with a Rh content of less than 0.1% by mass. The first purification catalyst section 3a is arranged on the hydrocarbon adsorption section 2 side, and the second purification catalyst section 3b can be provided on the first purification catalyst section 3a.
[0089] The first purification catalyst portion preferably contains a cerium oxide-zirconia composite oxide (CeO2-ZrO2). The content of CeO2 in the cerium oxide-zirconia composite oxide is preferably greater than 0 mass% and less than 30 mass%, and more preferably within the range of 15 mass% to 30 mass%. In the case where the first purification catalyst portion contains cerium oxide-zirconia with a CeO2 content within the range of 15 mass% to 30 mass%, hydrocarbons desorbed from the hydrocarbon adsorption portion can be directly oxidized, so it is preferred.
[0090] A second example of an embodiment of the present invention is an exhaust gas purification catalyst comprising: a substrate; a hydrocarbon adsorption portion on the substrate comprising a hydrocarbon adsorbing material and at least one of Rh and Pt, with a Pd content of 0.1 mass % or less; and a purification catalyst portion on the hydrocarbon adsorption portion comprising at least one of Pd and Pt, with a Rh content of 0.1 mass % or less.
[0091] Figure 3 FIG. 1 shows a part of a cross section of an exhaust gas purification catalyst according to a second example. The exhaust gas purification catalyst 10 includes: a substrate 1; a hydrocarbon adsorbing portion 2 provided on the substrate 1; and a purification catalyst portion 3 on the hydrocarbon adsorbing portion 2. Figure 3 In the figure, reference numeral 30 denotes an exhaust gas flow path.
[0092] Hereinafter, each part constituting the exhaust gas purifying catalyst will be described.
[0093] Substrate
[0094] The substrate can use a known substrate for exhaust gas catalyst. As the material of the substrate, ceramics and metals can be listed. As the ceramic substrate, refractory ceramic materials can be listed, for example, cordierite, hydrocarbons, mullite, silica-alumina, alumina, etc. can be listed. As the metal substrate, refractory metals can be listed, such as stainless steel, etc. In addition, the shape of the substrate can use a substrate such as a honeycomb-shaped substrate having a plurality of cavities in the form of parallel and fine flow paths inside the substrate. As the shape of such a substrate, a wall flow type substrate, an overflow type substrate, etc. can be listed.
[0095] Hydrocarbon adsorption unit
[0096] Regarding the hydrocarbon adsorption part, a slurry-like composition for the hydrocarbon adsorption part is prepared, which includes the following hydrocarbon adsorption materials and inorganic oxides such as alumina particles, oxygen absorption and release materials, alumina sol, silica sol, and zirconia sol. The hydrocarbon adsorption material is a hydrocarbon adsorption material containing a porous zeolite containing the above-mentioned metal or a hydrocarbon adsorption material composed of a porous zeolite containing the above-mentioned metal. The slurry-like composition for the hydrocarbon adsorption part is applied to a substrate, dried as needed, and calcined to form a hydrocarbon adsorption part. As the oxygen absorption and release material, inorganic oxides such as cerium oxide-zirconia composite oxide can be listed. The inorganic oxide can contain rare earths. The composition for the hydrocarbon adsorption part used to form the hydrocarbon adsorption part can contain Rh and / or Pt. In the case where the hydrocarbon adsorbent contained in the composition for the hydrocarbon adsorption part is a hydrocarbon adsorbent composed of MSE type zeolite in porous zeolite, the content of the hydrocarbon adsorbent is preferably 10% by mass or more and 85% by mass or less, more preferably 50% by mass or more and 75% by mass or less, and further preferably 60% by mass or more and 70% by mass or less, relative to the solid content of the composition for the hydrocarbon adsorption part. In the case where the hydrocarbon adsorption part contains Rh and / or Pt, the total content of Rh and Pt contained in the hydrocarbon adsorption part is preferably 0.05% by mass or more and 0.8% by mass or less, more preferably 0.14% by mass or more and 0.7% by mass or less, and further preferably 0.2% by mass or more and 0.5% by mass or less, relative to the solid content of the composition for the hydrocarbon adsorption part. By containing Rh and / or Pt in the hydrocarbon adsorption part, hydrocarbons desorbed in the hydrocarbon adsorption part can be efficiently purified.
[0097] Regarding the purification catalyst part, a slurry-like composition for the purification catalyst part is prepared, and the slurry-like composition for the exhaust gas purification catalyst part is applied to the hydrocarbon adsorption part formed on the substrate, dried as needed, and calcined to form the purification catalyst part. The elements that will become the catalytically active components, the NOx absorbing material, the catalyst carrier, the stabilizer as needed, the binder, other components, and water are mixed and stirred to produce a slurry-like composition for the purification catalyst part. As the binder, an inorganic binder such as a water-soluble solution of alumina sol can be used. In the case where the exhaust gas purification catalyst includes each layer of an oxidation catalyst layer, a NOx absorbing layer, and a reduction catalyst layer, the composition for the exhaust gas purification catalyst part constituting each layer can use a composition for the purification catalyst part containing catalytically active elements required for the catalytic activity of each layer.
[0098] The purification catalyst portion includes a first purification catalyst portion including Rh and a second purification catalyst portion including Pd, the first purification catalyst portion being arranged on the hydrocarbon adsorption portion side, and when the second purification catalyst portion is provided on the first purification catalyst portion, a first purification catalyst portion composition including Rh and a second purification catalyst portion composition including Pd are prepared. In addition, when the hydrocarbon adsorption portion includes the above-mentioned hydrocarbon adsorbing material and Rh, a purification catalyst portion composition including Pd is prepared.
[0099] The first purification catalyst unit composition contains Rh and / or Pt. The total content of Rh and Pt in the first purification catalyst unit composition is preferably 0.1 mass % to 1.8 mass % relative to the solid content of the first purification catalyst unit composition, more preferably 0.2 mass % to 1.2 mass %, and further preferably 0.5 mass % to 1.0 mass %.
[0100] Preferably, the first catalyst portion composition contains a cerium oxide-zirconia composite oxide (CeO2-ZrO2) in which the content of CeO2 is preferably greater than 0 mass% and less than 30 mass%, more preferably in the range of 15 mass% to 30 mass%. In this specification, a cerium oxide-zirconia composite oxide containing more ZrO2 than CeO2 in the range of 15 mass% to 30 mass% is also referred to as "ZC composite oxide". Relative to the solid content of the first purification catalyst portion composition, the content of ZC composite oxide in the first catalyst portion composition is preferably 30 mass% to 80 mass%, more preferably 50 mass% to 80 mass%, and further preferably 55 mass% to 75 mass%.
[0101] The first purification catalyst unit composition may contain other platinum group metals other than Rh and Pt. Relative to the total amount of platinum group metals contained in the first purification catalyst unit composition, the content of other platinum group metals other than Rh and Pt in the first catalyst unit composition is preferably less than 50% by mass. Preferably, the first purification catalyst unit composition does not substantially contain Pd. The first catalyst unit composition does not substantially contain Pd, which means that, when Pd is included, it is less than 0.1 mass relative to the solid content of the first catalyst unit composition, and preferably Pd is 0 mass% relative to the solid content of the first catalyst unit composition. Platinum group metals refer to Pt, Pd, Rh, Ir, Ru and Os.
[0102] The second purification catalyst unit composition or the purification catalyst unit composition contains Pd and / or Pt. The total content of Pd and Pt in the second purification catalyst unit composition is preferably 0.5 mass % or more and 8.0 mass % or less, more preferably 0.8 mass % or more and 7.0 mass % or less, and further preferably 1.5 mass % or more and 3.5 mass % or less relative to the solid content of the second purification catalyst unit composition.
[0103] The second purification catalyst unit composition preferably contains a cerium oxide-zirconia composite oxide (CeO2-ZrO2) in which the content of CeO2 is in the range of 25 mass % to 55 mass %. In this specification, a cerium oxide-zirconia composite oxide containing less ZrO2 than CeO2 in the range of 25 mass % to 55 mass % is also referred to as "CZ composite oxide". Relative to the solid content of the second purification catalyst unit composition, the content of CZ composite oxide in the second catalyst unit composition is preferably 20 mass % or more and 80 mass % or less, more preferably 30 mass % or more and 70 mass % or less, and further preferably 40 mass % or more and 60 mass % or less.
[0104] The second purification catalyst portion composition may contain other platinum group metals other than Pd and Pt. The content of other platinum group metals other than Pd and Pt in the second purification catalyst portion composition is preferably less than 50 mass % relative to the total amount of platinum group metals contained in the second purification catalyst portion composition.
[0105] Preferably, the second purification catalyst unit composition or the purification catalyst unit composition does not substantially contain Rh. The second purification catalyst unit composition does not substantially contain Rh, which means that, when Rh is contained, it is less than 0.1% by mass relative to the solid content of the second purification catalyst unit composition, and preferably Rh is 0% by mass relative to the solid content of the second purification catalyst unit composition.
[0106] Purification catalyst part composition, the first purification part composition or the second purification catalyst part composition can be manufactured by any known means.For example, a compound containing specific elements Rh, Pt or Pd can be contacted with an inorganic oxide carrier (such as cerium oxide-zirconia composite oxide) to obtain an inorganic oxide carrier of a load specific element, so as to make a purification catalyst part composition containing the inorganic oxide carrier. As a method for attaching a specific element to an inorganic oxide carrier, for example, evaporation method, impregnation method, precipitation method, ion exchange method, etc. can be listed. As an evaporation method, an inorganic oxide, a compound containing a specific element can be listed and placed in a container, and normal temperature or heating evaporates the compound containing the element, so as to attach to an inorganic oxide method. As an impregnation method, an inorganic oxide can be listed and immersed in a liquid mixed with a compound containing the element and a solvent, and the mixed solution is heated and dried under normal pressure or reduced pressure, so as to attach to an inorganic oxide method. As the impregnation method, the incipient wetness method, the evaporation drying method, the pore filling method, the spray method, the equilibrium adsorption method, etc. can be listed. As the precipitation method, the mixing method, the sedimentation method, etc. can be listed. The zeolite to which the compound containing the element is attached can be dried at a temperature of, for example, above 80°C and below 150°C, and the drying time is above 0.5 hours and within 5 hours. The pressure during drying is not particularly limited, and can be atmospheric pressure (0.1MPa) or under reduced pressure below 0.1MPa. The zeolite attached with the element can be dried as needed and further heat-treated. In order to prevent the pore defects of the zeolite, the heat treatment temperature can be in the range of above 200°C and below 800°C, or in the range of above 400°C and below 700°C.
[0107] In the case of the exhaust gas purification catalyst of the first example in which the purification catalyst portion includes: a first purification catalyst portion including at least one of Rh and Pt, and a second purification catalyst portion including at least one of Pd and Pt, the first purification catalyst portion can be formed by applying the first purification catalyst portion composition on the hydrocarbon adsorption portion formed on the substrate, drying it as needed, and calcining it. Next, the second purification catalyst portion composition is applied on the first purification catalyst portion, drying it as needed, and calcining it, so that the second purification catalyst portion can be formed. The first purification catalyst portion and the second purification catalyst portion can be distinguished by quantitatively analyzing the cross section of the exhaust gas purification catalyst by an electron beam microanalyzer (EPMA: Electron Probe Micro Analyzer). The platinum group metals contained in the first purification catalyst portion are mainly Rh and Pt, and Pd is substantially not contained. The first purification catalyst portion refers to a portion where, when the cross section of the exhaust gas purification catalyst is quantitatively analyzed by EPMA, the content of Pd is 0.1% by mass or less relative to 100% by mass of the solid content of the composition for the first catalyst portion. The platinum group metals contained in the second purification catalyst portion are mainly Pd and Pt, and substantially do not contain Rh. The second purification catalyst portion refers to a portion where, when a cross section of the exhaust gas purification catalyst is cut and quantitatively analyzed by EPMA, the content of Rh is 0.1% by mass or less relative to 100% by mass of the solid content of the composition for the second catalyst portion.
[0108] In the case of the second example of the exhaust gas purification catalyst in which the hydrocarbon adsorption portion includes a hydrocarbon adsorption material and Rh, a purification catalyst composition containing Pd is applied to the hydrocarbon adsorption portion formed on the substrate, dried as needed, and calcined to form the purification catalyst portion. The purification catalyst portion can be identified by quantitatively analyzing the cross section of the exhaust gas purification catalyst by an electron beam microanalyzer (EPMA: Electron Probe Micro Analyzer). The platinum group metals contained in the purification catalyst portion are mainly Pd and Pt, and substantially no Rh is contained. The purification catalyst portion refers to the following part: when the cross section of the exhaust gas purification catalyst is quantitatively analyzed by EPMA, Rh is 0.1% by mass or less relative to 100% by mass of the solid content of the composition for the purification catalyst portion.
[0109] The exhaust gas purification catalyst can also be used in a selective catalytic reduction (SCR) system. The selective catalytic reduction (SCR) system can reduce NOx to N2 by reacting with nitrogen compounds such as ammonia or urea or hydrocarbons.
[0110] Exhaust gas purification catalysts can be used to purify exhaust gas from internal combustion engines such as gasoline engines and diesel engines that use fuel as a power source, and can adsorb and store hydrocarbons at relatively high temperatures, thereby improving hydrocarbon removal performance and NOx reduction performance.
[0111] Exhaust gas purification system
[0112] Now, an exhaust gas purification system using the above-mentioned exhaust gas purification catalyst will be described.
[0113] Figures 4 to 6 Exhaust gas purification systems of first to third examples of the present invention are shown.
[0114] like Figure 4 As shown, the exhaust gas purification system 100 of the first example includes: an internal combustion engine 20; a first exhaust gas purification catalyst 40 provided on the upstream side in an exhaust gas flow path 30 connected to the internal combustion engine; and a second exhaust gas purification catalyst 10 provided on the downstream side in the exhaust gas flow direction relative to the first exhaust gas purification catalyst 40 in the exhaust gas flow path 30. The second exhaust gas purification catalyst 10 is the exhaust gas purification catalyst 10 of the first example or the second example of the present invention described above. When the second exhaust gas purification catalyst 10 is provided on the downstream side in the exhaust gas flow path 30 relative to the first exhaust gas purification catalyst, the exhaust gas having a relatively high temperature of about 1000° C. exhausted from the internal combustion engine 20 passes through the first exhaust gas purification catalyst 40, and the temperature of the exhaust gas decreases, so that thermal degradation of the porous zeolite contained in the hydrocarbon adsorption portion of the second exhaust gas purification catalyst can be suppressed, and the hydrocarbon adsorption capacity of the hydrocarbon adsorption portion can be maintained. The second exhaust gas purification catalyst 10 as the above-mentioned exhaust gas purification catalyst has a platinum group content ratio within the range of 0.1 g / L or more and 3.0 g / L or less relative to the volume of the second exhaust gas purification catalyst. When the platinum group metal content ratio in the second exhaust gas purification catalyst 10 as the above-mentioned exhaust gas purification catalyst is within the range of 0.1 g / L or more and 3.0 g / L or less relative to the volume of the second exhaust gas purification catalyst, the desorbed hydrocarbons can be purified more efficiently. It should be noted that in Figure 4 In the figure, although two examples of the exhaust gas purification catalysts are shown, namely the first exhaust gas purification catalyst 40 and the second exhaust gas purification catalyst 10, the exhaust gas purification catalysts may be more than three. For example, other exhaust gas purification catalysts may be provided on the downstream side of the exhaust gas flow direction compared with the second exhaust gas purification catalyst 10. As other exhaust gas purification catalysts provided on the downstream side compared with the second exhaust gas purification catalyst 10, it may be the exhaust gas purification catalyst 10 of the first example or the second example of the present invention described above, or it may be other exhaust gas purification catalysts. As the shape of the substrate used in other exhaust gas purification catalysts, a wall flow type substrate, an overflow type substrate, etc. may be appropriately used.
[0115] like Figure 5As shown, the exhaust gas purification system 200 of the second example comprises: an internal combustion engine 20; and a single exhaust gas purification catalyst 10 arranged in an exhaust gas flow path 30 connected to the internal combustion engine, and the exhaust gas purification catalyst 10 is the exhaust gas purification catalyst of the present invention described above. The exhaust gas purification system 200 of the second example of the present invention comprises the exhaust gas purification catalyst 10 of the present invention having high hydrocarbon removal performance, so when it is applied to an internal combustion engine with a relatively small exhaust gas volume, while making the exhaust gas purification performance sufficient, the number of the exhaust gas purification catalyst 10 can be made single, so that both high purification performance and low cost can be achieved.
[0116] like Figure 6 As shown, the exhaust gas purification system 300 of the third example comprises an internal combustion engine 20 and a plurality of exhaust gas purification catalysts 10, 50, 60 arranged in an exhaust gas flow path 30 connected to the internal combustion engine, wherein the first exhaust gas purification catalyst 10 arranged at the most upstream side in the exhaust gas flow direction is the exhaust gas purification catalyst of the present invention described above. Figure 6 The third example of the exhaust gas purification system 300 shown shows an example of having three exhaust gas purification catalysts in the exhaust gas flow path 30, namely, the most upstream exhaust gas purification catalyst 10, the second exhaust gas purification catalyst 50, and the third exhaust gas purification catalyst 60. The exhaust gas purification system 300 only needs to have two or more exhaust gas purification catalysts in the exhaust gas flow path 30, and the number of exhaust gas purification catalysts is not limited. The exhaust gas purification system 300 of the third example of the present invention has a plurality of exhaust gas purification catalysts in the exhaust gas flow path 30, and the first exhaust gas purification catalyst 10 arranged on the most upstream side is the exhaust gas purification catalyst of the present invention, which can more efficiently purify the desorbed hydrocarbons through the downstream exhaust gas purification catalyst.
[0117] Method for treating exhaust gas
[0118] An example method for treating exhaust gas according to an embodiment of the present invention includes the following steps: contacting combustion exhaust gas containing hydrocarbons with an exhaust gas purification catalyst according to an embodiment of the present invention, and after adsorbing the hydrocarbons on the exhaust gas purification catalyst, desorbing the hydrocarbons from the exhaust gas purification catalyst at a temperature above 200°C.
[0119] Example
[0120] The present invention will be further described below based on examples and comparative examples. The present invention is not limited to these examples.
[0121] Production of MSE zeolite
[0122] Deionized water (pure water), potassium hydroxide, aluminum hydroxide, N,N,N',N'-tetraalkylbicyclo[2.2.2]oct-7-ene-2,3:5,6-dipyrrolidinium iodide and colloidal silica (LUDOX (registered trademark) HS-40, manufactured by Sigma-Aldrich Japan Co., Ltd.) were prepared and mixed to obtain a raw material composition having the following composition in a molar ratio of each raw material.
[0123] SiO2 / Al2O3=20
[0124] K / Si=0.38
[0125] N,N,N',N'-Tetraalkylbicyclo[2.2.2]oct-7-ene-2,3-(5,6-bipyrrolidinium) iodide / Si=0.1
[0126] H2O / Si=30
[0127] The obtained raw material composition is filled into a sealed container, and heated at 160°C for 16 days in a static state to crystallize it. The raw material composition after crystallization is subjected to solid-liquid separation, washed with deionized water, and the crystals are recovered. The obtained crystals are dried at 100°C for 8 hours, and heat-treated at 600°C for 1 hour in an air atmosphere to obtain an MSE type zeolite. The fact that the obtained zeolite is an MSE type can be confirmed by measuring it using a powder X-ray diffraction device. In the X-ray diffraction spectrum using a powder X-ray diffraction device, when there is a diffraction peak at the above-mentioned diffraction angle (2θ) position, it can be confirmed to be an MSE type zeolite. The diffraction angle (2θ) position of the diffraction peak in the X-ray diffraction spectrum is the same as the diffraction angle (2θ) position of the diffraction peak in the X-ray diffraction spectrum published by the International Zeolite Society. Figure 7 The X-ray diffraction spectrum of the obtained MSE type zeolite is shown.
[0128] The obtained MSE type zeolite had a composition in which the molar ratios of the components were as follows.
[0129] SiO2 / Al2O3=20
[0130] Production of EON type zeolite
[0131] Deionized water (pure water), sodium hydroxide, sodium aluminate, and No. 3 sodium silicate were prepared and mixed to obtain a raw material composition having the following composition in a molar ratio of each raw material.
[0132] SiO2 / Al2O3=10
[0133] Na / Si=0.44
[0134] H2O / Si=20
[0135] The obtained raw material composition is filled into a sealed container, and heated at 150°C for 7 days in a static state to crystallize it. The raw material composition after crystallization is subjected to solid-liquid separation, washed with deionized water, and the crystals are recovered. The obtained crystals are dried at 100°C for 8 hours, and heat-treated at 600°C for 1 hour in an air atmosphere to obtain EON-type zeolite. The fact that the obtained zeolite is EON-type can be confirmed by measuring using a powder X-ray diffraction device. In the X-ray diffraction spectrum using a powder X-ray diffraction device, when there is a diffraction peak at the above-mentioned diffraction angle (2θ) position, it can be confirmed to be an EON-type zeolite. The diffraction angle (2θ) position of the diffraction peak in the X-ray diffraction spectrum is the same as the diffraction angle (2θ) position of the diffraction peak in the X-ray diffraction spectrum disclosed by the International Zeolite Society. Figure 8 The X-ray diffraction spectrum of the obtained EON type zeolite is shown.
[0136] The obtained EON type zeolite had a composition in which the molar ratios of the components were as follows.
[0137] SiO2 / Al2O3=7.6
[0138] Na / Al=0.95
[0139] Example 1
[0140] Manufacturing of hydrocarbon adsorbents
[0141] 1 g of the obtained MSE zeolite was immersed in 10 g of a 1 mol / L aqueous solution of ammonium chloride at 80°C, subjected to solid-liquid separation, and washed with deionized water to obtain NH4-type MSE zeolite. 1 g of the obtained NH4-type MSE zeolite was immersed in 100 g of a 0.25 mol / L aqueous solution of copper (II) acetate at 60°C, subjected to solid-liquid separation, and washed with deionized water to recover the wet powder. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE zeolite having the following molar ratio composition was obtained. The obtained Cu ion-exchanged MSE zeolite was used as a hydrocarbon adsorbent.
[0142] SiO2 / Al2O3=20
[0143] Cu / Al=0.75
[0144] Example 2
[0145] 1 g of the obtained MSE type zeolite is immersed in 10 g of a 1 mol / L ammonium chloride aqueous solution at 80°C, solid-liquid separation is performed, and the solution is washed with deionized water to obtain an NH4 type MSE type zeolite. 1 g of the obtained NH4 type MSE type zeolite is immersed in 100 g of a 0.25 mol / L cesium chloride aqueous solution, solid-liquid separation is performed, and the solution is washed with deionized water to obtain a wet Cs type MSE type zeolite. The obtained Cs-containing MSE type zeolite is dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cs ion-exchanged MSE type zeolite having the following molar ratio composition is obtained. The MSE type zeolite is exchanged with Cs and H ions. The obtained MSE type zeolite containing Cs is used as a hydrocarbon adsorbent.
[0146] SiO2 / Al2O3=20
[0147] Cs / Al=0.22
[0148] Example 3
[0149] 1 g of the obtained EON type zeolite was immersed in 10 g of a 1 mol / L aqueous solution of ammonium chloride at 60°C, subjected to solid-liquid separation, and washed with deionized water to obtain NH4 type EON type zeolite. 1 g of the obtained NH4 type EON type zeolite was immersed in 2.5 g of 1 mol / L sulfuric acid at 60°C, subjected to solid-liquid separation, and washed with deionized water to obtain H type EON type zeolite. 1 g of the obtained H type EON type zeolite was immersed in 10 g of a 0.50 mol / L aqueous solution of copper (II) acetate, subjected to solid-liquid separation, and washed with deionized water to recover the wet powder. The obtained wet powder was dried at 100°C for 8 hours and heat treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged EON type zeolite having the following molar ratio composition was obtained. The obtained Cu ion-exchanged EON type zeolite was used as a hydrocarbon adsorbent.
[0150] SiO2 / Al2O3=20
[0151] Cu / Al=0.5
[0152] Example 4
[0153] 1 g of the wet powder of the H-type EON zeolite obtained in the above Example 3 was immersed in 5.0 g of a 0.30 mol / L cesium carbonate aqueous solution at 60°C, solid-liquid separation was performed, and the wet powder was washed with deionized water to recover the wet powder. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cs ion-exchanged EON zeolite having the following molar ratio composition was obtained. The obtained Cs ion-exchanged EON zeolite was used as a hydrocarbon adsorbent.
[0154] SiO2 / Al2O3=13
[0155] Cs / Al=0.25
[0156] Comparative Example 1
[0157] 1 g of commercially available H-type BEA zeolite (SiO2 / Al2O3 molar ratio = 37) was suspended in 5 g of a 60°C copper (II) acetate aqueous solution, and the wet powder was recovered by evaporation to dryness. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a BEA zeolite containing Cu having the following molar ratio composition was obtained. The obtained BEA zeolite containing Cu was used as a hydrocarbon adsorbent.
[0158] SiO2 / Al2O3=37
[0159] Cu / Al=0.88
[0160] Comparative Example 2
[0161] 1 g of BEA zeolite (SiO2 / Al2O3 molar ratio = 37) was immersed in 10 g of a 0.1 mol / L aqueous solution of ammonium chloride at 60°C, subjected to solid-liquid separation, and washed with deionized water to obtain NH4-type BEA zeolite. 1 g of the obtained NH4-type BEA zeolite was immersed in 30 g of a 0.05 mol / L aqueous solution of cesium acetate at 60°C, subjected to solid-liquid separation, and washed with deionized water to recover the wet powder. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a BEA zeolite containing Cs having the following molar ratio composition was obtained. The BEA zeolite was exchanged with Cs and H ions. The obtained BEA zeolite containing Cs was used as a hydrocarbon adsorbent.
[0162] SiO2 / Al2O3=37
[0163] Cs / Al=0.18
[0164] Comparative Example 3
[0165] Except that MFI zeolite (SiO2 / Al2O3 molar ratio = 39) was used instead of BEA zeolite, the same operation as in Comparative Example 3 was performed to obtain MFI zeolite containing Cs. MFI zeolite was ion-exchanged with Cs and H. The composition of MFI zeolite containing Cs is shown in the following molar ratio. The obtained MFI zeolite containing Cs was used as a hydrocarbon adsorbent.
[0166] SiO2 / Al2O3=39
[0167] Cs / Al=0.17
[0168] Comparative Example 4
[0169] The wet powder of the NH4-type MSE-type zeolite obtained in Example 1 was dried at 100°C for 8 hours, heat-treated at 550°C for 3 hours in an air atmosphere, and used as a hydrocarbon adsorbent as it is.
[0170] Preparation of test samples
[0171] The raw material composition or each zeolite was filled into a vinyl chloride tube having a diameter of 30 mm and compression-molded to prepare a measurement sample.
[0172] SiO2 / Al2O3 molar ratio
[0173] The Si and Al amounts in the measurement sample were measured by elemental analysis using a scanning fluorescent X-ray analyzer (ZSX PrimusII, manufactured by Rigaku Corporation), and the SiO2 / Al2O3 ratio was calculated from the measured Si and Al amounts.
[0174] Cu / Al Ratio
[0175] The amount of Cu and the amount of Al in the sample were measured by elemental analysis using the scanning fluorescent X-ray analyzer, and the amount of Cu and Cu / Al were calculated. In Table 1, the amount of Cu is recorded as the metal content ratio, and Cu / Al is recorded as the metal / Al ratio.
[0176] Cs / Al ratio
[0177] The amount of Cs and the amount of Al in the sample were measured by elemental analysis using the scanning fluorescent X-ray analyzer, and Cs / Al was calculated. In Table 1, the amount of Cs is recorded as the metal content ratio, and Cs / Al is recorded as the metal / Al ratio.
[0178] Desorption / adsorption of toluene
[0179] Each hydrocarbon adsorbent of the Examples and Comparative Examples was heated from 50° C. to 500° C. by a temperature rise reaction method while flowing toluene, and the adsorption temperature, desorption temperature, adsorption amount, and desorption amount of toluene were measured.
[0180] Specifically, 0.1 g of the measurement sample of each hydrocarbon adsorbent was filled into a quartz reaction tube of a flow reactor, and a fixed bed flow reactor was used as the flow reactor. While the evaluation gas containing 71 ppm of toluene was circulated at 1 L / min, the temperature was raised from 50°C to 500°C at a heating rate of 20°C / min by a temperature rise reaction method to adsorb and desorb toluene. In the toluene adsorption and desorption measurement of zeolite, the decrease in the detection amount of the downstream detector (VMS-1000F, manufactured by Shimadzu Corporation) relative to the flow amount of toluene was taken as the adsorption amount and the purification amount. The adsorption and desorption of hydrocarbons were detected in the region where the value above the flow amount flowing to the hydrocarbon adsorbent was detected. The ratio of the total molar amount ZD2 of toluene desorbed from the hydrocarbon adsorbent at 200°C or less to the total molar amount ZD1 of toluene adsorbed at 50°C or more and less than 200°C (ZD2 / ZD1×100) was taken as the desorption amount / adsorption amount of toluene. The results are shown in Table 1.
[0181] Measurement conditions
[0182] Evaluation gas: 71 ppm toluene, the balance nitrogen (N2).
[0183] Heat Treatment
[0184] Each of the hydrocarbon adsorbents of Examples 1, 2, 4 and Comparative Examples 1 to 4 was heat-treated under the following conditions.
[0185] (1) Temperature: 850°C
[0186] (2) Duration: 25 hours
[0187] (3) Atmosphere: An atmosphere containing 10% by volume of water vapor (H2O), wherein water vapor is vaporized from a tank containing water and the saturated water vapor pressure is adjusted by temperature to produce an atmosphere containing 10% by volume of water vapor.
[0188] (4) Sample gas flow mode: The sample gas described in (5) below was flowed at 3 L / min for 80 seconds and Air was flowed at 3 L / min for 20 seconds alternately.
[0189] (5) Sample gas: The sum of C3H6, O2 and N2 is 3 L / min, C3H6 is 70 mL / min, O2 is 70 mL / min, and the balance is nitrogen (N2).
[0190] Peak intensity ratio of X-ray diffraction spectrum
[0191] The hydrocarbon adsorbents before and after the heat treatment of Examples 1, 2, 4 and Comparative Examples 1 to 4 were measured using an X-ray diffractometer (model: MiniFlex600, manufactured by Rigaku Corporation), and the peak intensity ratio of the X-ray diffraction spectrum before and after the heat treatment was calculated using the following formula. The diffraction angle (2θ) positions of the diffraction peaks used to calculate the peak intensity ratio are: the strongest peak near 2θ = 21.7° for MSE zeolite, the strongest peak near 2θ = 22.4° for BEA zeolite, the strongest peak near 2θ = 22.9° for MFI zeolite, and the strongest peak near 2θ = 25.6° for EON zeolite. The higher the peak intensity ratio calculated, the more it indicates that the zeolite can maintain its crystal structure even after the heat treatment.
[0192] Peak intensity ratio (%) = (peak intensity after heat treatment / peak intensity before heat treatment) × 100
[0193] [Table 1]
[0194]
[0195] As shown in Table 1, it can be confirmed that the hydrocarbon adsorbents of Examples 1 to 4 (porous zeolites containing specific metals) have a low desorption / adsorption amount of toluene compared to the zeolites of Comparative Examples 2 to 4, that is, the desorption amount is small relative to the adsorption amount, and toluene can be stored up to a temperature of about 200°C, and toluene can be desorbed from the hydrocarbon adsorbent at a relatively high temperature of 200°C or above. In addition, it can be confirmed that the hydrocarbon adsorbents of Examples 1, 2, and 4 have a high peak intensity ratio of the X-ray diffraction spectrum compared to the zeolite of Comparative Example 1, and maintain crystals even after heat treatment, and have excellent heat resistance. It should be noted that zeolites generally have a low skeleton density (the total amount of Si and Al per unit volume), and the more metal is introduced, the lower the heat resistance. In contrast, MSE-type zeolites or EON-type zeolites, which are porous zeolites, have a higher skeleton density than BEA-type zeolites and MFI-type zeolites, and are therefore considered to have better heat resistance. Although the peak intensity ratio of the hydrocarbon adsorbent of Example 3 was not measured, it is considered that the peak intensity ratio is at least higher than that of the BEA zeolite of Comparative Example 1. This is because, although the metal amount is the same in Example 3 and Comparative Example 1, the skeleton density of Example 3 is higher.
[0196] Example 5
[0197] 1 g of the obtained MSE zeolite was immersed in 10 g of a 1 mol / L aqueous solution of ammonium chloride at 80°C, subjected to solid-liquid separation, and washed with deionized water to obtain NH4-type MSE zeolite. 1 g of the obtained NH4-type MSE zeolite was immersed in 9.5 g of a 0.05 mol / L aqueous solution of copper (II) acetate at 60°C, subjected to solid-liquid separation, and washed with deionized water to recover the wet powder. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE zeolite having the following molar ratio composition was obtained. The obtained Cu ion-exchanged MSE zeolite was used as a hydrocarbon adsorbent.
[0198] SiO2 / Al2O3=20
[0199] Cu / Al=0.19
[0200] Example 6
[0201] The same operation as in Example 5 was performed to obtain an NH4-type MSE-type zeolite. The same operation as in Example 5 was performed except that 1 g of the obtained NH4-type MSE-type zeolite was immersed in 6 g of a 0.05 mol / L copper (II) acetate aqueous solution at 60°C to obtain a Cu ion-exchanged MSE-type zeolite. The composition of the obtained Cu ion-exchanged MSE-type zeolite is shown below. The obtained Cu ion-exchanged MSE-type zeolite was used as a hydrocarbon adsorbent.
[0202] SiO2 / Al2O3=20
[0203] Cu / Al=0.15
[0204] Example 7
[0205] The same operation as in Example 5 was performed to obtain NH4 type MSE type zeolite. 1 g of the obtained NH4 type MSE type zeolite was immersed in 5.3 g of a 0.05 mol / L cesium carbonate aqueous solution, solid-liquid separation was performed, and the wet powder was washed with deionized water to recover the wet powder. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cs ion-exchanged MSE type zeolite having the following molar ratio composition was obtained. The MSE type zeolite was exchanged with Cs and H ions. The obtained MSE type zeolite containing Cs was used as a hydrocarbon adsorbent.
[0206] SiO2 / Al2O3=20
[0207] Cs / Al=0.07
[0208] Example 8
[0209] The same operation as in Example 5 is performed to obtain NH4-type MSE-type zeolite. 1 g of the obtained NH4-type MSE-type zeolite is immersed in 10 g of 0.1 mol / L sulfuric acid at 80°C, solid-liquid separation is carried out, and the zeolite is washed with deionized water to obtain H-type MSE-type zeolite. 1 g of the obtained H-type MSE-type zeolite is immersed in 1 g of 0.2 mol / L copper (II) acetate aqueous solution, and the wet powder is recovered. The obtained wet powder is dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE-type zeolite having the following molar ratio composition is obtained. The obtained Cu ion-exchanged MSE-type zeolite is used as a hydrocarbon adsorbent.
[0210] SiO2 / Al2O3=22
[0211] Cu / Al=0.21
[0212] Example 9
[0213] The same operation as in Example 5 is performed to obtain NH4 type MSE type zeolite. 1 g of the obtained NH4 type MSE type zeolite is immersed in 10 g of 1 mol / L sulfuric acid at 80°C, solid-liquid separation is carried out, and the zeolite is washed with deionized water to obtain H type MSE type zeolite. 1 g of the obtained H type MSE type zeolite is immersed in 1 g of 0.2 mol / L copper (II) acetate aqueous solution, and the wet powder is recovered. The obtained wet powder is dried at 100°C for 8 hours and heat treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE type zeolite having the following molar ratio composition is obtained. The obtained Cu ion-exchanged MSE type zeolite is used as a hydrocarbon adsorbent.
[0214] SiO2 / Al2O3=58
[0215] Cu / Al=0.50
[0216] Example 10
[0217] The same operation as in Example 5 is performed to obtain NH4-type MSE-type zeolite. 1 g of the obtained NH4-type MSE-type zeolite is immersed in 10 g of 3 mol / L sulfuric acid at 80°C, solid-liquid separation is carried out, and the zeolite is washed with deionized water to obtain H-type MSE-type zeolite. 1 g of the obtained H-type MSE-type zeolite is immersed in 1 g of 0.2 mol / L copper (II) acetate aqueous solution, and the wet powder is recovered. The obtained wet powder is dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE-type zeolite having the following molar ratio composition is obtained. The obtained Cu ion-exchanged MSE-type zeolite is used as a hydrocarbon adsorbent.
[0218] SiO2 / Al2O3=76
[0219] Cu / Al=0.70
[0220] Embodiment 11
[0221] The same operation as in Example 5 is performed to obtain NH4-type MSE-type zeolite. 1 g of the obtained NH4-type MSE-type zeolite is immersed in 10 g of 5 mol / L sulfuric acid at 80°C, solid-liquid separation is carried out, and the zeolite is washed with deionized water to obtain H-type MSE-type zeolite. 1 g of the obtained H-type MSE-type zeolite is immersed in 1 g of 0.2 mol / L copper (II) acetate aqueous solution to recover the wet powder. The obtained wet powder is dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE-type zeolite having the following molar ratio composition is obtained. The obtained Cu ion-exchanged MSE-type zeolite is used as a hydrocarbon adsorbent.
[0222] SiO2 / Al2O3=181
[0223] Cu / Al=1.65
[0224] Example 12
[0225] 1 g of the obtained MSE zeolite was immersed in 6.7 g of 6 mol / L sulfuric acid at 100°C, solid-liquid separation was performed, and the mixture was washed with deionized water to obtain H-type MSE zeolite. 1 g of the obtained H-type MSE zeolite was suspended in 5.8 g of 0.05 mol / L copper (II) acetate aqueous solution, and the wet powder was recovered by evaporation. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a Cu ion-exchanged MSE zeolite having the following molar ratio composition was obtained. The obtained Cu ion-exchanged MSE zeolite was used as a hydrocarbon adsorbent.
[0226] SiO2 / Al2O3=200
[0227] Cu / Al=2.09
[0228] Example 13
[0229] 1 g of the obtained MSE zeolite was immersed in 6.7 g of 6 mol / L sulfuric acid at 100°C, solid-liquid separation was performed, and the mixture was washed with deionized water to obtain H-type MSE zeolite. 1 g of the obtained H-type MSE zeolite was suspended in 5.2 g of a mixed aqueous solution of 0.03 mol / L gallium (III) nitrate and 0.015 mol / L platinum nitrate, and the wet powder was recovered by evaporation to dryness. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, an MSE zeolite containing Ga and Pt having the following molar ratio composition was obtained. The MSE zeolite containing Ga and Pt was used as a hydrocarbon adsorbent.
[0230] SiO2 / Al2O3=200
[0231] Ga / Al=1.74
[0232] Pt / Al=0.42
[0233] Embodiment 14
[0234] 1 g of the obtained MSE zeolite was immersed in 6.7 g of 6 mol / L sulfuric acid at 100°C, solid-liquid separation was performed, and the mixture was washed with deionized water to obtain H-type MSE zeolite. 1 g of the obtained H-type MSE zeolite was suspended in 11 g of 0.05 mol / L tin (II) acetate aqueous solution, and the wet powder was recovered by evaporation to dryness. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, an MSE zeolite containing Sn having the following molar ratio composition was obtained. The obtained MSE zeolite containing Sn was used as a hydrocarbon adsorbent.
[0235] SiO2 / Al2O3=200
[0236] Sn / Al=0.93
[0237] Comparative Example 5
[0238] 1 g of commercially available H-type BEA zeolite (SiO2 / Al2O3 molar ratio = 37) was suspended in 5 g of 0.05 mol / L copper (II) acetate aqueous solution, and the wet powder was recovered by evaporation to dryness. The obtained wet powder was dried at 100°C for 8 hours and heat-treated at 550°C for 3 hours in an air atmosphere. Thus, a BEA zeolite containing Cu having the following molar ratio composition was obtained. The obtained BEA zeolite containing Cu was used as a hydrocarbon adsorbent.
[0239] SiO2 / Al2O3=37
[0240] Cu / Al=0.37
[0241] Regarding each hydrocarbon adsorbent of Examples 5 to 14 and Comparative Example 5, the same operation as in Examples 1 to 4 and Comparative Example was performed to measure the samples, the SiO2 / Al2O3 molar ratio, the Cu / Al ratio and the Cs / Al ratio.
[0242] Ga / Al ratio and Pt / Al ratio
[0243] The amount of Ga, the amount of Pt, and the amount of Al in the sample were measured by elemental analysis using the scanning fluorescent X-ray analyzer, and Ga / Al and Pt / Al were calculated. In Example 13, the amount of Ga was 1.9% by mass, the amount of Pt was 1.3% by mass, Ga / Al was 1.74, and Pt / Al was 0.42. In Table 2, the sum of the amount of Ga and the amount of Pt is recorded as the metal content ratio, and the sum of Ga / Al and Pt / Al is recorded as the metal / Al ratio.
[0244] Sn / Al ratio
[0245] The amount of Sn and the amount of Al in the sample were measured by elemental analysis using the scanning fluorescent X-ray analyzer, and Sn / Al was calculated. In Table 2, the amount of Sn is recorded as the metal content ratio, and Sn / Al is recorded as the metal / Al ratio.
[0246] Desorption / adsorption of toluene
[0247] Each hydrocarbon adsorbent of Examples 5 to 14 and Comparative Example 5 was heated from 50° C. to 500° C. by a temperature rise reaction method while passing toluene and water, and the adsorption temperature, desorption temperature, adsorption amount, and desorption amount of toluene were measured.
[0248] Specifically, 0.1 g of the measurement sample of each hydrocarbon adsorbent is filled into a quartz reaction tube of a flow reactor (a fixed bed flow reactor is used as the flow reactor), and while an evaluation gas set to an atmospheric atmosphere containing 71 ppm of toluene and 10% by volume of water vapor is circulated at 1 L / min, the temperature is raised from 50°C to 500°C at a heating rate of 20°C / min by a temperature rise reaction method to adsorb and desorb toluene. In the toluene adsorption and desorption measurement of zeolite, the decrease in the amount detected by the downstream detector (VMS-1000F, manufactured by Shimadzu Corporation) relative to the flow amount of toluene is taken as the adsorption amount and the purification amount. The adsorption and desorption of hydrocarbons are detected in the region where a value above the flow amount flowing to the hydrocarbon adsorbent is detected. The ratio of the total molar amount ZD2 of toluene desorbed from the hydrocarbon adsorbent at 170°C or less to the total molar amount ZD1 of toluene adsorbed at 50°C or more and less than 170°C (ZD2 / ZD1×100) is taken as the desorption amount / adsorption amount of toluene. The results are shown in Table 2.
[0249] Since the adsorption and desorption behavior of toluene in the presence of water becomes complicated due to adsorption, desorption, and re-adsorption, and the adsorption, desorption, and re-adsorption behaviors vary depending on the SiO2 / Al2O3 ratio, metal amount, and metal type, the evaluation was conducted based on a temperature of 170°C at which only adsorption and desorption can be compared.
[0250] Measurement conditions
[0251] Evaluation gas: 71 ppm toluene, the balance nitrogen (N2).
[0252] Atmosphere: An atmosphere containing 10% by volume of water vapor (H2O), wherein water vapor is vaporized from a tank containing water and the saturated water vapor pressure is adjusted by temperature to produce an atmosphere containing 10% by volume of water vapor.
[0253] BET surface area
[0254] For each hydrocarbon adsorbent of Examples 5, 11, 13, 14 and Comparative Example 5, the BET specific surface area was calculated by the BET method based on the nitrogen adsorption isotherm measured in accordance with ISO 9277 (JIS Z8330: 2013).
[0255] Heat treatment, toluene desorption / adsorption, peak intensity ratio, BET specific surface area
[0256] For each hydrocarbon adsorbent of Examples 12 to 14 and Comparative Example 5, after heat treatment under the above-mentioned conditions, the same operations as those of each hydrocarbon adsorbent of Example 1 etc. were carried out under the above-mentioned conditions to measure the desorption / adsorption amount of toluene, the peak intensity ratio of the X-ray diffraction spectrum and the BET specific surface area.
[0257] In addition, in Comparative Example 5, after the heat treatment, it was confirmed by powder X-ray diffraction that the framework structure of the BEA-type zeolite was not maintained, and therefore adsorption measurement was not performed.
[0258] [Table 2]
[0259]
[0260] As shown in Table 2, it can be confirmed that the hydrocarbon adsorbents of Examples 5 to 12 (porous zeolites containing specific metals) have lower desorption / adsorption amounts of toluene than the zeolite of Comparative Example 5, that is, the desorption amount is small relative to the adsorption amount, and toluene can be stored up to a temperature of about 170°C, which is easy to evaluate the adsorption and desorption behavior of toluene with respect to the hydrocarbon adsorbent, and toluene can be desorbed from the hydrocarbon adsorbent at a relatively high temperature of 170°C or higher. In addition, it can be confirmed that the hydrocarbon adsorbents of Examples 12 to 14 also desorb and adsorb toluene after heat treatment, and have heat resistance. The zeolite of Comparative Example 5 does not adsorb toluene after heat treatment.
[0261] As shown in Table 2, it was confirmed that the hydrocarbon adsorbents of Examples 12 to 14 had a higher peak intensity ratio in the X-ray diffraction spectrum than the zeolite of Comparative Example 5, maintained crystals even after heat treatment, and had excellent heat resistance.
[0262] As shown in Table 2, the BET specific surface area ratio B / A of the hydrocarbon adsorbents before and after heat treatment of Examples 13 and 14 is within the range of 0.5 or more and 0.9 or less. The structure of the porous zeolite using the hydrocarbon adsorbent changes little before and after heat treatment, and the structure is maintained, which has heat resistance.
[0263] Industrial Applicability
[0264] The hydrocarbon adsorbing material according to the present invention adsorbs hydrocarbons and can store the adsorbed hydrocarbons until a relatively high temperature, and can desorb the adsorbed and stored hydrocarbons at a relatively high temperature at which the catalyst can be activated, so when used as a hydrocarbon adsorption part of an exhaust gas purification catalyst, the exhaust gas purification performance can be improved. In addition, the exhaust gas purification catalyst using the hydrocarbon adsorbing material can be suitably used for purifying exhaust gas discharged from an internal combustion engine of a four-wheeled vehicle, a two-wheeled motorcycle, etc.
[0265] Description of Reference Numerals
[0266] 1: substrate; 1a: chamber; 1b: partition wall; 2: hydrocarbon adsorption section; 3: purification catalyst section; 3a: first purification catalyst section; 3b: second purification catalyst section; 10: exhaust gas purification catalyst (first exhaust gas purification catalyst or second exhaust gas purification catalyst); 20: internal combustion engine; 30: exhaust gas flow path; 40, 50: exhaust gas purification catalyst; 100, 200, 300: exhaust gas purification system.
Claims
1. An exhaust gas purification catalyst comprising: a substrate; a hydrocarbon adsorption portion including a hydrocarbon adsorbing material on the substrate; and a purification catalyst portion on the hydrocarbon adsorption portion, The hydrocarbon adsorbent contains a porous zeolite containing a metal outside the zeolite framework, wherein the metal is at least one metal selected from the group consisting of Li, Na, K, Rb, Cs, Ca, Sr, Ba, Ni, Cu, Zn, Ga, Rh, Pd, Sn, Sc and Pt, The content ratio of the metal is 9 mass % or less relative to the porous zeolite containing the metal, The molar ratio of the metal to Al contained in the porous zeolite, that is, the metal / Al ratio, is within a range of 0.05 to 2.
5. The porous zeolite is MSE type zeolite or EON type zeolite, The porous zeolite comprises large tunnel-type pores and small cages whose largest ring is less than an eight-membered ring. In the porous zeolite, at least a portion of the metal is present in cages of small pores, The SiO2 / Al2O3 molar ratio of the porous zeolite is greater than or equal to 20 and less than or equal to 600.
2. The exhaust gas purification catalyst according to claim 1, wherein: The purification catalyst portion includes: a first purification catalyst portion including at least one of Rh and Pt; and a second purification catalyst portion including at least one of Pd and Pt, wherein the first purification catalyst portion is arranged on the hydrocarbon adsorbing portion side and the second purification catalyst portion is provided on the first purification catalyst portion.
3. The exhaust gas purification catalyst according to claim 2, wherein: The first purification catalyst portion includes a ceria-zirconia composite oxide CeO 2 —ZrO 2 in which a content of CeO 2 is within a range of 15 mass % or more and 30 mass % or less.
4. An exhaust gas purification catalyst comprising: a substrate; a hydrocarbon adsorption portion on the substrate containing a hydrocarbon adsorption material and Rh; and a purification catalyst portion on the hydrocarbon adsorption portion containing Pd, The hydrocarbon adsorbent contains a porous zeolite containing a metal outside the zeolite framework, wherein the metal is at least one metal selected from the group consisting of Li, Na, K, Rb, Cs, Ca, Sr, Ba, Ni, Cu, Zn, Ga, Rh, Pd, Sn, Sc and Pt, The content ratio of the metal is 9 mass % or less relative to the porous zeolite containing the metal, The molar ratio of the metal to Al contained in the porous zeolite, that is, the metal / Al ratio, is within a range of 0.05 to 2.
5. The porous zeolite is MSE type zeolite or EON type zeolite, The porous zeolite comprises large tunnel-type pores and small cages whose largest ring is less than an eight-membered ring. In the porous zeolite, at least a portion of the metal is present in cages of small pores, The SiO2 / Al2O3 molar ratio of the porous zeolite is greater than or equal to 20 and less than or equal to 600.
5. The exhaust gas purification catalyst according to any one of claims 1 to 4, wherein The metal is at least one selected from the group consisting of Cs, Ni, Cu, Zn, Ga, Rh, Pd, Sn, Sc, and Pt.
6. The exhaust gas purification catalyst according to any one of claims 1 to 4, wherein The molar ratio of the metal to Al contained in the porous zeolite, that is, the metal / Al ratio is within a range of 0.07 to 2.
16.
7. The exhaust gas purification catalyst according to any one of claims 1 to 4, wherein The porous zeolite contains phosphorus.
8. The exhaust gas purification catalyst according to claim 7, wherein: The P / Al molar ratio in the porous zeolite containing phosphorus is 0.4 or more and 1.1 or less.
9. The exhaust gas purification catalyst according to any one of claims 1 to 4, wherein The BET specific surface area A of the porous zeolite is 400 m 2 / g and above 1000m 2 / g or less.
10. The exhaust gas purification catalyst according to claim 9, wherein The specific surface area ratio B / A of the BET specific surface area A of the porous zeolite before heat treatment to the BET specific surface area B of the porous zeolite after heat treatment satisfying the heat treatment conditions (1) to (5) below is within the range of 0.35 or more and 1 or less, Heat treatment conditions: (1) Temperature: 850°C; (2) Duration: 25 hours; (3) Atmosphere: an atmosphere containing 10% by volume of water vapor, wherein water vapor is vaporized from a tank containing water and the saturated water vapor pressure is adjusted by temperature to produce an atmosphere containing 10% by volume of water vapor; (4) Sample gas circulation mode: In the ignition combustion and filling modes, alternately circulate the sample gas (5) at 3 L / min for 80 seconds and circulate air at 3 L / min for 20 seconds; (5) Sample gas: The sum of C3H6, O2 and N2 is 3 L / min, C3H6 is 70 mL / min, O2 is 70 mL / min, and the balance is N2.
11. The exhaust gas purification catalyst according to any one of claims 1 to 4, wherein The MSE zeolite has a peak intensity at a diffraction angle 2θ position where the diffraction angle 2θ of the (420) plane in the X-ray diffraction spectrum is 21.7°±1.0°, and a peak intensity ratio D / C of a peak intensity C of the (420) plane of the MSE zeolite before heat treatment to a peak intensity D of the (420) plane of the MSE zeolite after heat treatment satisfying the following heat treatment conditions (1) to (5) is within a range of 0.3 or more and 1.5 or less, (1) Temperature: 850°C; (2) Duration: 25 hours; (3) Atmosphere: an atmosphere containing 10% by volume of water vapor, wherein water vapor is vaporized from a tank containing water and the saturated water vapor pressure is adjusted by temperature to produce an atmosphere containing 10% by volume of water vapor; (4) Sample gas circulation mode: In the ignition combustion and filling modes, alternately circulate the sample gas (5) at 3 L / min for 80 seconds and circulate air at 3 L / min for 20 seconds; (5) Sample gas: The sum of C3H6, O2 and N2 is 3 L / min, C3H6 is 70 mL / min, O2 is 70 mL / min, and the balance is N2.
12. An exhaust gas purification system comprising: internal combustion engine; a first exhaust gas purification catalyst provided on an upstream side in an exhaust gas flow passage connected to the internal combustion engine; and a second exhaust gas purification catalyst provided in the exhaust gas flow path on the downstream side of the first exhaust gas purification catalyst in the exhaust gas flow direction; The second exhaust gas purification catalyst is the exhaust gas purification catalyst according to any one of claims 1 to 11. A content ratio of the platinum group metal in the second exhaust gas purification catalyst is 0.1 g / L or more and 3.0 g / L or less relative to the volume of the second exhaust gas purification catalyst.
13. An exhaust gas purification system comprising: Internal combustion engines; and a single exhaust gas purification catalyst located in an exhaust gas flow path connected to the internal combustion engine, The exhaust gas purification catalyst is the exhaust gas purification catalyst according to any one of claims 1 to 11.
14. An exhaust gas purification system comprising: Internal combustion engines; and a plurality of exhaust gas purification catalysts provided in an exhaust gas flow path connected to the internal combustion engine; Among the plurality of exhaust gas purification catalysts, the first exhaust gas purification catalyst disposed on the most upstream side in the exhaust gas flow direction is the exhaust gas purification catalyst according to any one of claims 1 to 11.
15. A method for treating exhaust gas, comprising the steps of: A combustion exhaust gas containing hydrocarbons is brought into contact with the exhaust gas purification catalyst according to any one of claims 1 to 11, and after the hydrocarbons are adsorbed on the exhaust gas purification catalyst, the hydrocarbons are desorbed from the exhaust gas purification catalyst at a temperature of 170° C. or higher.
Citation Information
Patent Citations
Use of cold start catalysts and exhaust systems
JP2014519975A
Age-resistant Rh-zeolite catalyst
CN102665905A
Catalyst and manufacturing method of catalyst
CN107398297A
Hydrocarbon adsorbent for exhaust gas and exhaust gas cleaning catalyst using it
JP2004105821A
Exhaust gas purifying catalyst and production method of the same
JP2004209323A